Answer:
2 m
Step-by-step explanation:
Here the area and the lengths of the two parallel sides of this trapezoid are given:
A = 7m^2, b1 = 3 m and b2 = 4 m. What's missing is the width of the trapezoid.
First we write out the formula for the area of a trapezoid:
b1 + b2
A = --------------- * w, where w represents the width of the figure.
2
We need to solve this for the width, w. Multiplying both sides of the above equation by
2
------------
b1 + b2
results in
2A
------------ = w
b1 + b2
Substituting 7 m^2 for A, 3 m for b1 and 4 m for b2 results in
2(7 m^2) 14 m^2
w = ------------------ = ---------------- = 2 m
(3 + 4) m 7 m
The missing dimension is the width of the figure. This width is 2 m.
Its a monomial and it has 4 terms
Answer:
7. r = -5
8. x = -1
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Step-by-step explanation:
<u>Step 1: Define</u>
r + 2 - 8r = -3 - 8r
<u>Step 2: Solve for </u><em><u>r</u></em>
- Combine like terms: -7r + 2 = -3 - 8r
- Add 8r to both sides: r + 2 = -3
- Subtract 2 on both sides: r = -5
<u>Step 3: Check</u>
<em>Plug in r into the original equation to verify it's a solution.</em>
- Substitute in <em>r</em>: -5 + 2 - 8(-5) = -3 - 8(-5)
- Multiply: -5 + 2 + 40 = -3 + 40
- Add: -3 + 40 = -3 + 40
- Add: 37 = 37
Here we see that 37 does indeed equal 37.
∴ r = -5 is a solution of the equation.
<u>Step 4: Define equation</u>
-4x = x + 5
<u>Step 5: Solve for </u><em><u>x</u></em>
- Subtract <em>x</em> on both sides: -5x = 5
- Divide -5 on both sides: x = -1
<u>Step 6: Check</u>
<em>Plug in x into the original equation to verify it's a solution.</em>
- Substitute in <em>x</em>: -4(-1) = -1 + 5
- Multiply: 4 = -1 + 5
- Add: 4 = 4
Here we see that 4 does indeed equal 4.
∴ x = -1 is a solution of the equation.
g(x) cannot have an inverse because it gives the same output value for two individual input values.
In this case, g(x) is 5 when x is both 3 and -1. Hence, g(x) does not have an inverse.
Let me know if you have any questions, thanks!